Advancing Sustainability: Green Product Satisfaction, Circularity, and Sustainable Development - Kremmydas, Christakis; Kostis, Pantelis C. (International Journal of Social Ecology and Sustainable Development (IJSESD), 2024)
This research focuses on sustainable consumption and production (SCP) to balance economic growth with ecological preservation. It assesses Greek consumers' attitudes, satisfaction, and knowledge about green products through questionnaires, analyzing the interplay of these factors in consumer satisfaction and highlighting the role of awareness in the green market. The study also compares these findings with Romanian consumer behavior to understand cultural and socioeconomic influences. Results show that positive attitudes towards green products and access to information significantly enhance consumer satisfaction, a trend consistent across different cultures. However, a lack of sustainability knowledge among youth presents an educational opportunity. The study advocates for strategic educational efforts to support SCP, emphasizing the need for well-informed product design, fair pricing, and clear communication to promote sustainable consumer habits, contributing to the broader SCP discourse and guiding future sustainable economy policies.